Research on The Party Leadership of The Communist Party of China (CPC): The Transformation from Agricultural Paradigm to Industrial Paradigm - Bin Wang; Chang-sheng Tang (International Journal of Management and Education in Human Development, 2022)
The promotion of Party leadership is very important not only to enhance the cohesion of the party in itself but also for the successful implementation of the national strategy. Since 1949, China has made remarkable achievements under the leadership of the CPC which has attracted worldwide attention. In the process of industrialization, China has accomplished the transformation from an agricultural paradigm to an industrial paradigm and the leadership of the CPC has been strengthened steadily. This paper mainly analyzes the evolution of the transformation of the industrialization paradigm and the leadership of the CPC from a historical and macro perspective. It can be concluded that the promotion of the leadership of the CPC and the transformation of the industrialization paradigm is not only an interactive relationship to China's national conditions but also an inevitable consequence of the process of world industrialization. The world industrialization paradigm has changed China, and the shift of China's industrial paradigm has changed the world too, which provides the Chinese solution to the promotion of party leadership and the realization of industrialization in other countries in the world.